Satisfaction with Work Life Balance: A Study of Women Police Personnel in Hyderabad - Vijayalakshmi, K. (Prabandhan: Indian Journal of Management, 2012)
This paper studies the WLB satisfaction of female police personnel who work at irregular hours in the midst of their domestic caring responsibilities by focusing on their perceptions of work responsibilities, their domestic caring responsibilities and their perception of work-life balance satisfaction. It was based on the structured survey through a questionnaire, with women police who work in Hyderabad police stations. The Findings suggest a need for change both in organizational and work policies for female police in Hyderabad.